MANAJEMEN PEMBINAAN CABANG OLAHRAGA ATLETIK DI PUSAT PENDIDIKAN DAN LATIHAN PELAJAR (PPLP) PROVINSI JAWA TENGAH - Rumini, Rumini (Journal of Physical Education Health and Sport, 2015)
Pembinaan prestasi olahraga di Pusat Pendidikan dan Latihan Pelajar (PPLP) Jawa Tengah merupakan wadah pembinaan prestasi atlet-atlet yang memiliki potensi olahraga di Jawa Tengah. Untuk meningkatkan prestasi optimal perlu adanya SDM pengelolaan yang kompeten. Di samping itu faktor penunjang seperti pendanaan dan sarana prasarana yang memadai akan menjadi efek samping dalam meraih prestasi yang tinggi. Melalui manajemen pembinaan yang baik prestasi olahraga di PPLP dapat ditingkatkanThe purpose of this research is to know the influence of the traditional game of rounders repetition techniques to increase gross motor skills of children SLB N Ungaran mild mental retardation. The method used in this study is the experimental method. This research is pretest posttest One Group Design. Methods of data analysis using the t test. Population and sample is a random sample of mild mental retardation children SLB N Ungaran totaling 7 children. All samples were given treatment repetition rounders game techniques.Gross motor research results with the t test there is the influence of the average results of a calculation using a mild mental retardation child hypothesis tests to run 1:43 (pre-test) and 2:57 (post-test), running 1:43 (pre-test) and 2:57 (post-test) , throws 1:29 (pre-test) and 2.71 (post-test), capturing 1:43 (pre-test) and 2:43 (post-test), hit 1:29 (pre-test) and 2:14 (post-test). Aspects that there is no influence, namely jumping 1.71 (pre-test) and 1:57 (post-test), jump 1:43 (pre-test) and 1:29 (post-test), kicking 1.71 (pre-test) and 1:29 (post-test) , In addition to every aspect of the average in the overall gross motor tests increased by an average of 1:44 (pre-test) and 2:07 (post-test). The conclusions in this study are repetition baseball gPembinaan prestasi olahraga di Pusat Pendidikan dan Latihan Pelajar (PPLP) Jawa Tengah merupakan wadah pembinaan prestasi atlet-atlet yang memiliki potensi olahraga di Jawa Tengah. Untuk meningkatkan prestasi optimal perlu adanya SDM pengelolaan yang kompeten. Di samping itu faktor penunjang seperti pendanaan dan sarana prasarana yang memadai akan menjadi efek samping dalam meraih prestasi yang tinggi. Melalui manajemen pembinaan yang baik prestasi olahraga di PPLP dapat ditingkatkaname techniques affect the increase in gross motor skills mild mental retardation children SLB N Ungaran